Survival of Vibrio parahaemolyticus at low temperatures under starvation conditions and subsequent resuscitation of viable, nonculturable cells. - Jiang, X (1996)
Morphological changes of Vibrio parahaemolyticus from rods to spheres took place after a culture was subjected to starvation at a wide range of temperatures. Scanning electron micrographs revealed that starved spherical cells gradually developed a rippled cell surface with blebs and an extracellular filamentous substance adhesive to the cell surface. Cells starved at a low temperature for certain intervals were counted by various bacterial enumeration methods, including plate count, direct viable count, and total cell count for both Kanagawa-positive and -negative strains. The results indicated that this species could reach the nonculturable stage in 50 to approximately 80 days during starvation at 3.5 degrees C. Kanagawa-negative strain 38C6 lost culturability more slowly than Kanagawa-positive strain 38C1 at low temperature. As detected by thiosulfate-citrate-bile salts-sucrose plate count, a high percentage of the surviving cells at 3.5 degrees C in starvation medium were possibly injured by the low temperature rather than by starvation. Both addition of nalidixic acid to the starved cultures and the most-probable-number method demonstrated that the cells recovered after a temperature upshift probably represented the regrowth of a few surviving cells. These surviving cells were capable of growth and multiplication with limited nutrients at an extraordinary rate when the temperature was upshifted.